1999
DOI: 10.1109/6046.784465
|View full text |Cite
|
Sign up to set email alerts
|

Face detection using quantized skin color regions merging and wavelet packet analysis

Abstract: Detecting and recognizing human faces automatically in digital images strongly enhance content-based video indexing systems. In this paper, a novel scheme for human faces detection in color images under nonconstrained scene conditions, such as the presence of a complex background and uncontrolled illumination, is presented. Color clustering and filtering using approximations of the YCbCr and HSV skin color subspaces are applied on the original image, providing quantized skin color regions. A merging stage is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
234
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(244 citation statements)
references
References 40 publications
(42 reference statements)
1
234
0
3
Order By: Relevance
“…Skin colors are distributed differently from hair colors, spreading more continuously, yet within a bounded range [5]. As we found that the illumination conditions have a greater influence on detection of skin than they do on hair, we decided to model the skin colors based on three illumination categories, namely, bright, standard, and dark.…”
Section: Skin Color Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin colors are distributed differently from hair colors, spreading more continuously, yet within a bounded range [5]. As we found that the illumination conditions have a greater influence on detection of skin than they do on hair, we decided to model the skin colors based on three illumination categories, namely, bright, standard, and dark.…”
Section: Skin Color Modelmentioning
confidence: 99%
“…Weights in (5) are chosen by a search over interval [0,1] in steps of 0.1 units so as to maximize correct hair pixel detection over a training set.…”
Section: Hair Color Modelmentioning
confidence: 99%
“…In six algorithms, The YcbCr approach observes skin color as 2D model and other as 3D model, they using Genetic Algorithm (GA) to training the boundary of several color models, their experiment shown that YcbCr color space is more recall oriented and RGB is a good tradeoff between recall and precision [6]. Christophe and Georgios using vector quantization technique [12], to quantize the image color, and construct a 3D skin color model that distributed in HSVand YcbCr color space, both colo models is constructed by 950 skin color samples which have been extracted from various still images and video frames. Jones and Rehg apply visualization techniques [7] to fetch out the shape of skin color distribution.…”
Section: Related Workmentioning
confidence: 99%
“…In [2,3], mean values and the corresponding variances were computed from face images to characterize different faces. Specifically, 3 mean values and 3 variances of the approximation image and 15 variances of details images form the feature vector.…”
Section: Main Menumentioning
confidence: 99%